Marketing and e-commerce in a service company. An empirical study. (LACCEI, 2024)
The general objective of this research was to determine how the marketing mix influences the e-commerce of the company Multicolor, San Juan de Lurigancho, Lima 2021. The research had a quantitative approach, basic, explanatory level and non-experimental cross-sectional design. The population under study consisted of 130 customers with respect to the 2020 sales of the Multicolor company, with a non-probabilistic sample by convenience, composed of 80 customers of the company. The applied technique was the survey. The instrument used was the questionnaire, which obtained a Cronbach's alpha of 0.816 for the marketing mix variable and 0.863 for the e-commerce variable, which means a high statistical reliability, and a content validation by experts of 100% for the Marketing Mix variable and 98% for the E-commerce variable, which means a high content validity for the questionnaire. Finally, it was determined that the marketing mix significantly influences the ecommerce of the company Multicolor, San Juan de Lurigancho, Lima 2021, demonstrated through the chi-square test with a value of (64.932) and with a significance level of 0.000 0.05, which clearly indicates that a good execution of e-commerce is determined or explained by a good execution of the marketing mix.